2023
DOI: 10.3390/ijms24021092
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Landscape of Bladder Cancer in Mexican Patients: KMT2D Mutations and chr11q15.5 Amplifications Are Associated with Muscle Invasion

Abstract: Bladder cancer (BC) is the most common neoplasm of the urinary tract, which originates in the epithelium that covers the inner surface of the bladder. The molecular BC profile has led to the development of different classifications of non-muscle invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer (MIBC). However, the genomic BC landscape profile of the Mexican population, including NMIBC and MIBC, is unknown. In this study, we aimed to identify somatic single nucleotide variants (SNVs) and copy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
(53 reference statements)
2
2
0
Order By: Relevance
“…4A). This frequency is consistent with previously reported in other MIBC cohorts 12,26,27 , highlighting their role as BC drivers.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…4A). This frequency is consistent with previously reported in other MIBC cohorts 12,26,27 , highlighting their role as BC drivers.…”
Section: Resultssupporting
confidence: 92%
“…The mutational landscape of our cohort was consistent with those found in other MIBC cohorts 12,26,27,56 . While mutations in genes such as TP53, ERCC2, RB1, ATM and FGFR3 are known to correlate with response to cisplatin-based NAC 57–63 , in our study, more SNVs in ERCC2, RB1 and ATM were found in R compared to NR, but no statistically significant differentiation was found 59,60,6467 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Perez-Montiel and colleagues have examined the genetic landscape of Mexican BC patients, a hitherto understudied population, and found a high frequency of mutations in TP53 and KMT2D, along with gains in 11q15.5 and 19p13.11-q12 and losses in 7q11.23. Furthermore, STAG2 mutations and 1q11.23 deletions were associated with NMIBC and a low histologic grade, which offers fresh perspectives for classifying BC subtypes [18].…”
mentioning
confidence: 99%